Nilai Humanisme dalam Serat Saptastha - Afiliasi Ilafi; Bani Sudardi; nfn Supana (Madah: Jurnal Bahasa dan Sastra, 2018)
The king is a leader as divine manifestation. Every command and decision must be obeyed and executed as evidence of devotion. The king who was still obeyed by his people despite experiencing uncommon events among the king is Hamengku Buwana VII. The story of Hamengku Buwana VII setback from the king’s chair is described in the contents of Serat Saptastha manuscript and stored in the museum Sonobudoyo Yogyakarta. Serat Saptastha manuscript belongs to the historical manuscript because it contains the history of the transition of power from Hamengku Buwana VII to his son named Pangeran Adipati Anom who then was crowned as Hamengku Buwana VIII after Hamengku Buwana VII chose to leave his kingdom and settle in Ambarukma. The method used in this paper is content analysis with literature sociology approach. This paper shows that the manuscript of Serat Saptastha can depict the figure of Hamengku Buwana VII as the king of courageous and authoritative despite the lengser keprabon experience. The image of humanism displayed by Hamengku Buwana VII in the Serat Saptastha shows the attitude of kawicaksanaan, courage, and dignity